Competencies of Indian Medical Graduates in delivering Effective Tuberculosis care: A mixed method study among doctors at Chennai, India - Sree Tirukkovalluri Sucharitha; Aravind Manoharan; Ezhilarasan Suganya; Sivaram Mahendran Balaji (Indian Association of Preventive and Social Medicine, 2023)
Background: In spite of the various advances in the Tuberculosis (TB) management system in our country, we are still struggling to achieve the End TB strategy. Addressing the health provider difficulties in TB care will definitely be potential tool to control TB. Objective: To assess the competency, challenges and solutions of Indian medical graduates to provide effective Tuberculosis care. Method: It is a mixed methodological study conducted among the Bachelor of Medicine and Bachelor of Surgery (MBBS) graduates practising in various parts of Chennai, Tamil Nadu, India. The competency of the Indian medical graduates in delivering TB care was assessed using a content validated e-survey questionnaire disseminated through social media affinity groups andfree listing;pile sorting and in-depth interview was done in the qualitative part. Results:The proportion of participants having good, fair and poor competency in providing effective TB care was 35%,19% and 46%, respectively. Various challenges in attaining good competency were enlisted by the participants through free listing, a smaller number of TB patients in private medical college has attained the highest Smith S value followed by other eleven challenges. Based on the pile sorting and in-depth interview various solutions have been suggested, with most of them emphasizing on compulsory TB chest clinic posting followed by others measures. Conclusion:The major reason identified in difficulties in delivering TB care was inadequate exposure in managing TB patients, incomplete knowledge on notification,referral and followup system. These lacunae can be overturned by compulsory posting in TB clinics during internship period, provision of required personal protective equipment (PPE) for doctors and patients in TB wards and outpatient department, mandatoryteaching on updates of TB management.